The impact of sport-specific achievement and affiliation motives on young athletes' dropout and persistence in elite sports - Schröder, S.; Knisel, E. (Scientific Journal of Sport and Performance, 2024)
This study aims to compare the sport specific achievement and affiliation motive structures of athletes who later decide to dropout or continue their elite sports career. In addition, groups of athletes were analyzed separately according to age, gender and type of sport in order to identify possible group differences. 146 young elite athletes were analyzed (64 girls, 82 boys, mean age: 13.55, SD = 1.14) and self reported about their motive structure. The data were collected using the German Achievement Motive Scale-Sport and the German Affiliation Motive Scale Sport. Significant differences were found between the athletes who dropped out from junior elite sports and athletes who continued in the fear of failure of the achievement motive. The analysis of gender differences shows that female athletes generally exhibited significantly higher levels of fear motives. We found no differences between female athletes who continue and discontinue the sport career. The male athletes who dropped out showed a higher level of the hope of affiliation und fear of rejection. When comparing the different age groups, it was found in the older age groups that the fear to fail motives differs significantly between the adherence and the dropout group. The results indicate that the fear of failure represents an unfavourable motivation profile for a long-term sporting career. Considering that the motivational structure has an impact on continuing a sports career the motivational profile has to be diagnosed at an early stage and then tackled accordingly in order to avoid an early dropout.